The Plays, Novels, Short Fiction and Non-Fiction of Jack Kahane. - PEARSON, NEIL (Obelisk: A History of Jack Kahane & the Obelisk Press, 2007)
A list of plays, novels, short fiction and non-fiction of Jack Kahane which include "Two Plays", "Laugh and Grow Rich", and, " Love's Wild Geese" is presented.